Evaluation of the Knowledge, Opinion, and Approaches of Pharmacists, Physicians, Dieticians, and the Public on Herbal Products Used for Weight Control and Slimming in Northern Cyprus - lzzet, Bariş Şendal; Yavuz, Hasan Ulaş; Yavuz, Dudu Özkum (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: This study explores the perspectives of Northern Cyprus (NC) pharmacists, physicians, dieticians, and the public regarding Herbal Products (HP) for Weight Control (WC) and slimming, contributing valuable insights to healthcare practices and public awareness. Aims: The objective is to comprehensively assess the knowledge, attitudes, and practices of community pharmacists, physicians/dieticians, and the general public in NC concerning WC and slimming. Additionally, the study aims to investigate their essential roles in dispensing HP for weight management, to enhance the safe and efficient use of herbal medicinal products and raise awareness about their effectiveness. Materials and Methods: The study involved 303 participants from the public, 24 pharmacists, and 21 physicians/dieticians who voluntarily participated through a combination of face-to-face and online distribution. Administering three questionnaires, the collected responses underwent statistical analysis using SPSS software. Results: Among public respondents, 71.95% reported not using HP for WC. For users, Senna was the preferred choice for 57.32%, followed by green tea at 51.22%. Pharmacists recommended Senna (58.33%) and green tea (50.00%) to their patients. Physicians/dieticians exhibited equal preferences, with 52.38% recommending green tea and Senna. Conclusion: Pharmacists play an essential role in raising awareness and educating patients on the safe utilization of HP for WC. However, a notable gap in their education regarding safe use, interactions, and side effects hinders optimal counseling and care. This study underscores the urgency for enhanced education and resources to address this knowledge deficit among pharmacists, healthcare professionals, and the public in NC.
Keywords: Obesity; Weight; Herbal Products; Northern Cyprus; Pharmacist